A [delta]18O isoscape for the shallow groundwater in the Baltic Artesian Basin - Raidla, Valle (Journal of hydrology, 2016)
The study presents a shallow groundwater isoscape for the Baltic region, which covers the major part of the Baltic Artesian Basin (BAB). BAB is an important palaeogroundwater reservoir, but prior to this study, little has been known about the spatial variability of δD and δ18O values in modern precipitation input across the region. To overcome this limitation, we hypothesized that the isotopic composition of shallow groundwater in the BAB could be used as a proxy for the mean weighted annual isotopic composition of local precipitation. However, the results of the study reveal many clear discrepancies between the isotopic composition of precipitation and shallow groundwater in the area. The isotopic composition of shallow groundwater is mostly biased towards isotopically depleted wintertime precipitation. We propose that the formation of shallow groundwater in the BAB area could be largely affected by variations in soil structure and land cover. The derived isoscape based on δ18O values of shallow groundwater in the BAB area is characterised by high spatial resolution and can therefore serve as a fairly reliable reference basis for further hydrogeological, ecological and forensic applications.